Many faces, one rule: the role of perceptual expertise in infants’ sequential rule learning - Bulf, Hermann; Brenna, Viola; Valenza, Eloisa; Johnson, Scott P.; Turati, Chiara (Frontiers in Psychology, 2015)
Rule learning is a mechanism that allows infants to recognize and generalize rule-like patterns, such as ABB or ABA. Although infants are better at learning rules from speech vs. non-speech, rule learning can be applied also to frequently experienced visual stimuli, suggesting that perceptual expertise with material to be learned is critical in enhancing rule learning abilities. Yet infants’ rule learning has never been investigated using one of the most commonly experienced visual stimulus category available in infants’ environment, i.e. faces. Here, we investigate 7-month-olds’ ability to extract rule-like patterns from sequences composed of upright faces and compared their results to those of infants who viewed inverted faces, which presumably are encountered far less frequently than upright faces. Infants were habituated with face triads in either an ABA or ABB condition followed by a test phase with ABA and ABB triads composed of faces that differed from those showed during habituation. When upright faces were used, infants generalized the pattern presented during habituation to include the new face identities showed during testing, but when inverted faces were presented, infants failed to extract the rule. This finding supports the idea that perceptual expertise can modulate 7-month-olds’ abilities to detect rule-like patterns.